Peningkatan Hasil Belajar Siswa Kelas X Melalui Pendekatan Smart Teaching Pada Materi Elastisitas Bidang Studi Ekonomi Di SMA Negeri 3 Painan - Hermus Gusni (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
Demand elasticity and supply elasticity are one of the competencies that must be mastered by the first year students of IPS and cross-interest in the field of economic study of SMA that use 13rd curriculummwhich is still too difficult to learn. Generally the value obtained in this material is still quite sufficient, although many of them are above the Minimum Completeness Criteria (KKM). Based on these facts, the authors are interested to analyze how to improve the learning outcomes of the first year students by using Smart Teaching approach in learning process.This activity uses Classroom Action Assessment (well known as PenelitianTindakanKelas) method with two activity cycles, the first cycle is before the use of Smart Teaching Approach, and the second cycle is using Smart Teaching Approach which was held in November 2017.The research tool is student questionnaire, formative test, and observation notes. The use of Smart Teaching approach in learning process has increased the student learning outcomes significantly because of the completion of the questions in a very fast and precise way, so it can be concluded that the use of this method is very effective to improve the learning outcomes and student achievement in economic subjects, especially elasticity.